ANALISIS KARAMAH INSANIYAH DALAM QS. AL-ISRA’ DAN RELEVANSINYA TERHADAP KEHIDUPAN KONTEMPORER - Achmad Nafis Qurtubi; Mei Arina Ilmi AS; Hirman Panggabean (Yayasan Baitul Hikmah al-Zain, 2025)
The concept of karamah insaniyah (human glory) is one of the main principles in the teachings of the Qur'an. Humans are honored by Allah with privileges that are not given to other creatures. This research examines the concept of karamah insaniyah in Surah Al-Isra’ (17): 80 and its relevance to contemporary life. Karamah insaniyah refers to the honor and glory given by Allah to human beings, distinguishing them from other creatures with various privileges, including reason, conscience, and moral ability. In the surah, Allah asserts that humans, regardless of race, nation or social status, are ennobled with basic rights that must be safeguarded, such as the right to life, the right to property, the right to procreate, the right to healthy thinking and the right to belief. This study aims to identify the meaning of the concept of karamah insaniyah in the Qur'anic perspective and analyze its relevance to the challenges of modern life, especially in fighting for human rights and gender equality. A descriptive-analytical qualitative approach is used to analyze Qur'anic texts and related literature, with the results showing that the principle of karamah insaniyah has broad implications in building a just society and respecting diversity, in line with the demands of the times that prioritize social justice and the protection of human rights. Karamah insaniyah provides a broad example in contemporary times, such as the behavior of a human being who remains istiqomah in doing good, as much as possible not violating the rules he acknowledges